Pre-service English Teachers’ Perceptions of Artificial Intelligence (AI) in Project Based Learning in Teaching English for Young Learners - Soviyah, Soviyah; Margana, Margana; Canape, Lorralie F.; Febriyanti, Febriyanti (Universitas Pendidikan Mandalika, 2025)
This study investigates how pre-service teachers specializing in Teaching English to Young Learners (TEYL) perceive and utilize Artificial Intelligence (AI) tools within Project-Based Learning (PBL), a context that remains underexplored in teacher education research. While AI adoption in education is growing, little is known about its role in supporting pre-service teachers’ creativity, pedagogical decision-making, and reflective practice in TEYL settings. To address this gap, a sequential explanatory mixed-methods design was employed, combining a survey of 50 Indonesian pre-service TEYL teachers with follow-up interviews with six purposively selected participants. This design was chosen to capture broad patterns of perception and then enrich them with contextualized insights. Data were collected using a questionnaire grounded in the Technology Acceptance Model (TAM) and semi-structured interviews, with quantitative analysis conducted through descriptive statistics and qualitative data analyzed thematically. Findings indicate high acceptance of AI, with participants valuing its ease of use and positive contribution to project work, particularly in brainstorming ideas and supporting design. At the same time, concerns emerged regarding overreliance, reduced critical thinking, and occasional unreliability of AI-generated content. These results highlight both the opportunities and risks of AI integration in TEYL teacher education. The study concludes that teacher education programs should embed AI literacy, promote reflective pedagogy, and design scaffolded PBL activities that balance technological support with the development of creativity, ethical awareness, and learner autonomy.